MILLIY KOMPANIYALARNING GLOBAL BOZORDAGI RAQOBAT SALOHIYATI VA UNI RIVOJLANTIRISH MEXANIZMLARI (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2026)
This article examines the key factors influencing the competitiveness of national companies in foreign markets. Particular attention is paid to product quality, innovation, pricing policy, marketing strategies, export potential, and government support mechanisms. The findings of the study contribute to the development of practical recommendations aimed at ensuring the sustainable development of national companies in international markets.